Human development as a general theory of social change: A multi-level and cross-cultural perspective - Christian Welzel; Ronald Inglehart; Hans-Dieter Klingemann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
This paper demonstrates that socioeconomic development, cultural modernization, and democratic regime performance constitute a coherent syndrome of social change'a syndrome whose common focus has not properly been specified by standard modernization theory. We specify this syndrome as Human Development, arguing that its three components have a common focus on individual choice. Socioeconomic development broadens individual choice by giving people more resources; cultural modernization gives rise to aspirations that lead people to seek for individual choice; and democracy extends individual choice by codifying legal opportunities. Analysis of data from 80 societies demonstrates: (1) that a universal resource-aspiration-opportunity syndrome is present at the individual, national and supra-national levels across 80 nations and 8 cultural zones; (2) that this Human Development syndrome is endogenously shaped by a causal effect from resources and aspirations on opportunities; and (3) that elite integrity or good governance is a strong exogenous determinant of the Human Development syndrome as a whole. – – Das vorliegende Papier zeigt, dass sozio-ökonomische Entwicklung, kulturelle Modernisierung und demokratische Regimeperformanz ein kohärentes Syndrom sozialen Wandels bilden - ein Syndrom, dessen integrierender Kern von der klassischen Modernisierungstheorie nicht hinreichend spezifiziert wurde. Wir spezifizieren diesen Kern mit dem Konzept der Humanentwicklung. Wir argumentieren, dass die drei Komponenten der Humanentwicklung dahingehend zusammenwirken, dass sie die individuelle Optionsvielfalt steigern. Sozio-ökonomische Entwicklung erweitert Optionen, indem sie den Individuen mehr Ressourcen verleiht; kulturelle Modernisierung mobilisiert Ansprüche, die die Individuen nach Optionsvielfalt streben lassen; und Demokratie sichert Optionen durch rechtliche Garantien. Eine Analyse der Weltwertestudien zeigt, dass es (1) einen universellen Nexus aus Ressourcen, Ansprüchen und Garantien gibt, der sich auf der individuellen, nationalen und supra-nationalen Ebene über 80 Gesellschaften und 8 Kulturzonen nachweisen lässt; (2) dass die endogene Genese dieses Syndroms der Humanentwicklung durch kausale Effekte von Ressourcen und Ansprüchen auf Garantien zustande kommt; und (3) dass regelkonformes Elitenverhalten eine exogene Determinante dieses Syndroms insgesamt ist.
Keywords: 300